Subtotal hysterectomy of ischemic uterus during caesarean section in buffaloes - SINGH, M P; PRASAD, J K; DAS, ARUP KUMAR; PRASAD, SHIV (The Indian Journal of Animal Reproduction, 2023)
Eight cases ofischemic/ necrosed uterus were detected during caesarean operation in buffaloes. Zone ofischemia wasidentified and quantified clinically in the gravid uterus during the operation. The percentage of ischemia / necrosis of the uterinebed ranged between 10 and 25%. After the manual removal of the dead foetus the portion ofischemic or necrosed uterus wasexcised along with the portion of peripheral healthy tissues of the gravid horn. Caesarean wound were closed routinely. Onebuffalo died but the other seven recovered uneventfully.
Keywords: Buffalo; dystocia; ischemia; uterus; subtotal/ partial hysterectomy